AVE 0991 Attenuates Pyroptosis and Liver Damage after Heatstroke by Inhibiting the ROS-NLRP3 Inflammatory Signalling Pathway. (19th August 2019) - Zhang, Ming; Zhu, Xintao; Tong, Huasheng; Lou, Anni; Li, Yue; Li, Yang; Su, Lei; Li, Xu
Abstract : We previously demonstrated that angiotensin-(1-7) (Ang-(1-7)), an essential endocrine factor, inhibits the NLRP3 inflammasome by regulating reactive oxygen species (ROS) in fibrotic livers. We also demonstrated that the NLRP3 inflammasome contributes to the liver damage induced by pyroptosis after heatstroke. However, the role of Ang-(1-7) in the hepatocytes under heat stress remains uncertain. We aimed to examine the change in angiotensin peptides in the livers affected by heatstroke and the effect on the ROS-NLRP3 inflammatory signalling pathway. In vivo, increased angiotensin II (Ang II) and decreased Ang-(1-7) in the serum of heatstroke patients suffering from hepatic dysfunction were observed. The change in angiotensin peptides was considered a potential biomarker that could be used to predict hepatic dysfunction. Enhanced Ang II and attenuated Ang-(1-7) levels were also observed in the liver tissue of heatstroke rats, which were consistent with their receptors and converting enzymes. Hepatic damage associated with increased ROS and protein expression levels of NOX4, NLRP3, caspase-1, and IL-1 β was attenuated by AVE 0991, an analogue of Ang-(1-7). In vitro, pyroptosis, characterized by activated caspase-1 and IL-1 β, was observed in hepatocytes under heat stress, which was enhanced by Ang II and attenuated by antioxidants, NOX4 siRNA, and AVE 0991. In summary, AVE 0991 attenuates pyroptosis and liver damage induced by heat stress by inhibiting the ROS-NLRP3 inflammatory signalling pathway.